The Effect of Sport Activities on Perceptual-motor Skills among Obese Children with Down Syndrome - Abdollah Ghasemi; Maryam Momeni; Mehdi Sohrabi (University of Social Welfare and Rehabilitation Sciences, 2015)
Objective: The aim of the present study was to investigate the effect of eight weeks selected sport trainings on perceptual- motor skills among typical obese girls and girls with Down syndrome (aged 7-13). Materials & Methods: In this quasi-experimental study with control group, 22 obese children with Down syndrome and 22 typical obese children who were selected purposefully participated in 24 purposeful sport training sessions. All groups were assessed with Bruininks-Oseretsky Test of Motor Proficiency before and after training sessions. Results: The findings showed that both groups of participants significantly developed in their gross motor skills (P<0.05) but not in fine skills. Also, the results indicated that obese children with Down syndrome had significantly (P<0.05) higher progress in both gross and fine motor skills than typical children. Conclusion: Despite of the variety of influential genetic and environmental constraints on obese children with Down syndrome they can develop their perceptual-motor skills via purposeful sport trainings such as play and leisure. Necessity of early perceptual-motor training is discussed.